UVA Radiation Enhances Lomefloxacin-Mediated Cytotoxic, Growth-Inhibitory and Pro-Apoptotic Effect in Human Melanoma Cells through Excessive Reactive Oxygen Species Generation - Beberok, Artur (Int J Mol Sci, 2020)
Melanoma, the most dangerous type of cutaneous neoplasia, contributes to about 75% of all skin cancer-related deaths. Thus, searching for new melanoma treatment options is an important field of study. The current study was designed to assess whether the condition of mild and low-dose UVA radiation augments the lomefloxacin-mediated cytotoxic, growth-inhibitory and pro-apoptotic effect of the drug in melanoma cancer cells through excessive oxidative stress generation. C32 amelanotic and COLO829 melanotic (BRAF-mutant) melanoma cell lines were used as an experimental model system. The combined exposure of cells to both lomefloxacin and UVA irradiation caused higher alterations of redox signalling pathways, as shown by intracellular reactive oxygen species overproduction and endogenous glutathione depletion when compared to non-irradiated but lomefloxacin-treated melanoma cells. The obtained results also showed that lomefloxacin decreased both C32 and COLO829 cells’ viability in a concentration-dependent manner. This effect significantly intensified when melanoma cells were exposed to UVA irradiation and the drug. For melanoma cells exposed to lomefloxacin or lomefloxacin co-treatment with UVA irradiation, the concentrations of the drug that decreased the cells’ viability by 50% (EC(50)) were found to be 0.97, 0.17, 1.01, 0.18 mM, respectively. Moreover, we found that the redox imbalance, mitochondrial membrane potential breakdown, induction of DNA fragmentation, and changes in the melanoma cells’ cell cycle distribution (including G(2)/M, S as well as Sub-G(1)-phase blockade) were lomefloxacin in a dose-dependent manner and were significantly augmented by UVA radiation. This is the first experimental work that assesses the impact of excessive reactive oxygen species generation upon UVA radiation exposure on lomefloxacin-mediated cytotoxic, growth-inhibitory and pro-apoptotic effects towards human melanoma cells, indicating the possibility of the usage of this drug in the photochemotherapy of malignant melanoma as an innovative medical treatment option which could improve the effectiveness of therapy. The obtained results also revealed that the redox imbalance intensification mediated by the phototoxic potential of fluoroquinolones may be considered as a more efficient treatment model of malignant melanoma and may constitute the basis for the development of new compounds with a high ability to excessive oxidative stress generation upon UVA radiation in cancer cells.